Efficient application programming interface for multi-dimensional modeling data - Jones, Norman L.; Wallace, Robert M.; Jones, Russell; Butler, Cary; Zundel, Alan (Journal of hydroinformatics, 2012)
This paper describes an Application Programming Interface (API) for managing multi-dimensional data produced for water resource computational modeling that is being developed by the US Army Engineer Research and Development Center (ERDC), in conjunction with Brigham Young University. This API, along with a corresponding data standard, is being implemented within ERDC computational models to facilitate rapid data access, enhanced data compression and data sharing, and cross-platform independence. The API and data standard are known as the eXtensible Model Data Format (XMDF), and version 1.3 is available for free download. This API is designed to manage geometric data associated with grids, meshes, riverine and coastal cross sections, and both static and transient array-based datasets. The inclusion of coordinate system data makes it possible to share data between models developed in different coordinate systems. XMDF is used to store the data-intensive components of a modeling study in a compressed binary format that is platform-independent. It also provides a standardized file format that enhances modeling linking and data sharing between models.